(untitled) (Journal of Imam Al-Kadhim College, 2025)
The research represents an important aspect of the Qur’anic study that researchers should pay attention to, by focusing on the structures of words and their use in the Holy Qur’an, with the aim of revealing the relationships linking the Qur’anic meaning and the linguistic structure, and revealing the semantic differences between the Qur’anic formula and the formula interpreted by it, which leads to reading the text within the limits of its realized formal structure, far from the sayings of deviation, assumption, and arbitrariness in guidance. The research concluded by saying that the assumed interpretive morphological formula is not suitable to replace the chosen Qur’anic formula, and is unable to accurately convey the meaning it conveys, since each morphological formula has its own significance, and the Qur’an employed its structures according to their various values ​​and arranged in a unique stylistic manner, representing the highest levels of rhetorical sublimity.